The effect of recurrent application of concentrated platelet-rich fibrin inside the extraction socket on the hard and soft tissues. a randomized controlled trial - Cezar Lahham; Mahmoud Abu Ta'a; Elias Lahham; Saleem Michael; Wael Zarif (BMC, 2023)
Abstract Background Platelet-rich fibrin (PRF) is commonly used for ridge preservation following tooth extraction. However, its effectiveness diminishes over a period of two weeks as it is resorbed and loses its biological activities. Therefore, this clinical study aims to evaluate the effect of recurrent application of concentrated PRF (C-PRF) inside the extraction socket on the hard and soft tissue alterations. Methods Twenty patients requiring single tooth extraction and replacement with a dental implant were randomized into one of two ridge preservation approaches: Advanced PRF plus alone (Control group) or advanced PRF plus with the recurrent application of a C-PRF inside the socket every two weeks for 2 months (four times). The ridge width, the ridge height, and the soft tissue thickness were assessed clinically at the baseline and reassessed after 3 months from tooth extraction during implant surgery. Then the amount of hard tissue loss and soft tissue alterations were calculated. Results There was a statistically significant difference in the amount of hard tissue loss between groups in the third month. The amount of horizontal ridge loss for the control and test groups were 2.9 ± 0.7 mm and 1.9 ± 0.5 mm, respectively (p-value < 0.05). The vertical bone loss for control and test groups were 1.8 ± 0.5 mm and 1.0 ± 0.3 mm, respectively (p-value < 0.05). Additionally, for the soft tissue thickness, there was no statistical difference between the groups (p-value > 0.05). Conclusion Within the limitations of this study, the recurrent application of C-PRF in the extraction socket could decrease the amount of ridge alteration following tooth extraction and may play a role in the bone regeneration procedures. Trial registration Registered on ClinicalTrials.gov (ID: NCT05492357, on 08/08/2022).